Literature Review: Traditional Indonesian Cakes as a Medium of Cultural Diplomacy - Febriani Lukitasari; Anistian Nur Azizah (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Food is widely recognized as a universal medium of communication that transcends linguistic and geographical boundaries. Within this context, culinary diplomacy emerges as an important strategy, where food embodies identity, history, and values. Indonesian traditional cakes (kue tradisional), such as Bika Ambon, Klepon, and Kue Clorot, carry cultural narratives that integrate heritage, symbolism, and local wisdom. Yet, their role in international cultural diplomacy has received limited attention. This study explores the potential of Indonesian traditional cakes as cultural ambassadors that reinforce the nation’s global presence. It addresses three central questions: (1) What symbolic meanings are embedded in traditional cakes? (2) How are these culinary traditions represented in practices of cultural diplomacy such as festivals and intercultural exchanges? (3) What challenges and opportunities arise in positioning them within Indonesia’s soft power framework? Applying a qualitative descriptive approach through literature review, cultural analysis, and case studies of culinary events, the study reveals that traditional cakes provide more than sensory enjoyment; they convey values of togetherness, hospitality, and cultural resilience. As accessible cultural symbols, they foster deeper connections and cross-cultural understanding. The paper concludes that Indonesian traditional cakes hold strong potential as instruments of cultural diplomacy, and their strategic promotion internationally can enhance Indonesia’s cultural image while nurturing intercultural harmony.